Clinical Reasoning: A 28-Year-Old Man with Subacute-Onset Ataxic Gait - Mauricio Benetti; Francisco Caiza-Zambrano; Ricardo Reisin; Claudia Shanley; Nicolás Roccatagliata; Luciana León-Cejas (The Neurohospitalist, 2026)
The diagnostic approach to subacute progressive polyneuropathy can be challenging, particularly when accompanied by systemic features. We present a 28-year-old man with subacute-onset ataxic gait. Four months before his initial evaluation at our center, he was assessed by orthopedics for a poorly differentiated tumor of the right tibia. He also reported intermittent fever and unintentional weight loss. Neurologic examination revealed marked weakness in all four limbs, with deep tendon reflexes absent in the lower extremities. Sensory testing demonstrated a stocking–glove distribution of hypoesthesia. Vibration and proprioception were decreased in all four limbs. Romberg sign was positive, and he had a broad-based ataxic gait with bilateral steppage. Nerve conduction studies demonstrated a demyelinating sensorimotor polyneuropathy. Initial laboratory and imaging studies showed thrombocytosis and radiologic evidence of organomegaly. This case highlights a stepwise diagnostic approach to progressive polyneuropathy with red flags for systemic disease and emphasizes the importance of integrating neurologic and systemic findings to expand the differential diagnosis, guide targeted investigations, and identify potentially treatable underlying conditions.